Giving callers the option to bypass the telephone waiting line in out-of-hours services: a comparative intervention study - J. F. Ebert; L. Huibers; B. Christensen; F. K. Lippert; M. B. Christensen (Taylor & Francis Group, 2019)
Objective: Acute out-of-hours (OOH) healthcare is challenged by potentially long waiting time for callers in acute need of medical aid. OOH callers must usually wait in line, even when contacting for highly urgent or life-threatening conditions. We tested an emergency access button (EAB), which allowed OOH callers to bypass the waiting line if they perceived their health problem as severe. We aimed to investigate EAB use and patient characteristics associated with this use. Design: Comparative intervention study. Setting: OOH services in two major Danish healthcare regions. Intervention: Giving callers the option to bypass the telephone waiting line by introducing an EAB. Participants: OOH service callers contacting during end of October to mid-December 2017. Main outcome measures: Proportions of EAB use, waiting time and background information on participants in two settings differing on organisation structure, waiting time and triage personnel. Results: In total, 97,791 out of 158,784 callers (61.6%) chose to participate. The EAB was used 2905 times out of 97,791 (2.97%, 95%CI 2.86; 3.08). Patient characteristics associated with increased EAB use were male gender, higher age, low education, being retired, and increasing announced estimated waiting time. In one region, immigrants used the EAB more often than native Danish callers. Conclusion: Only about 3% of all callers chose to bypass the waiting line in the OOH service when given the option. This study suggests that the EAB could serve as a new and simple tool to reduce the waiting time for severely ill patients in an OOH service telephone triage setting.Key Points Acute out-of-hours healthcare is challenged by overcrowding and increasing demand for services. This study shows that only approximately 3% of callers chose to bypass the telephone waiting queue when given the opportunity through an emergency access button. An emergency access button may serve as a new tool to help reduce the triage waiting time for severely ill patients in out-of-hours medical facilities.